(3GdUhGQe GdeGVjI aj JMbjb GdaQbI GdfGLjIs - (3eMeO egOj Hf GdMSf Hf CMeO GdMSjfj GdbRhjfj GdfLaj,J (B1300 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3hHYO ajbhd eMeO Hf GdMSf GdeOYh HegOj GdMSfj GdTgjQ HGdbRhjfj, deG JTYHJ GdePGgH hGdBQGA aj HjGf GdTQjYI GdZQGA s
(3BNQgG (B:s
(3hEjGce ef GdeJeScjf HSfJge GdbGVjf HCMcGege hTQjYJge hGdMeO ddg ChdkG hBNQkG eG CQOfG EjQGOg aj gPG GdcJGH GdoeSei HGdUhGQe GdeGVjI aj JMbjb GdaQb GdfGLjI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B114s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds